2017
DOI: 10.3390/ijms18081828
|View full text |Cite
|
Sign up to set email alerts
|

Circadian and Light Regulated Expression of CBFs and their Upstream Signalling Genes in Barley

Abstract: CBF (C-repeat binding factor) transcription factors show high expression levels in response to cold; moreover, they play a key regulatory role in cold acclimation processes. Recently, however, more and more information has led to the conclusion that, apart from cold, light—including its spectra—also has a crucial role in regulating CBF expression. Earlier, studies established that the expression patterns of some of these regulatory genes follow circadian rhythms. To understand more of this complex acclimation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 76 publications
4
40
0
Order By: Relevance
“…Although the effects of complementary far-red light with high light intensity are beneficial in many cases, if the plants were previously acclimated to a lower incident light intensity in growth chambers, the sudden increase in light intensity can bring harmful side effects like photoinhibition or loss of photosynthetic and anthocyanin pigments [60,61] during cold acclimation. It has also been shown that the lower R:FR ratio can increase the level of freezing tolerance via influencing the phytochrome signalling system [23,24,48]. Our results also proved that the elevated FR light in the spectra can greatly improve the frost tolerance, which can be further improved by increasing the light intensity in barley.…”
Section: The Freezing Testssupporting
confidence: 70%
See 2 more Smart Citations
“…Although the effects of complementary far-red light with high light intensity are beneficial in many cases, if the plants were previously acclimated to a lower incident light intensity in growth chambers, the sudden increase in light intensity can bring harmful side effects like photoinhibition or loss of photosynthetic and anthocyanin pigments [60,61] during cold acclimation. It has also been shown that the lower R:FR ratio can increase the level of freezing tolerance via influencing the phytochrome signalling system [23,24,48]. Our results also proved that the elevated FR light in the spectra can greatly improve the frost tolerance, which can be further improved by increasing the light intensity in barley.…”
Section: The Freezing Testssupporting
confidence: 70%
“…We must also consider that, in a natural environment, a decreased R:FR ratio occurs at sunset and, during this twilight period, the light intensity is gradually decreasing. Consequently, it seems to be evident that not only the spectrum but also the changing light intensity can be an important, external signal affecting gene regulation [21,24,47,48]. In tomatoes, monochromatic red and far-red light was tested for inducing cold tolerance.…”
Section: The Expression Of Hvcbf14 and Its Target Genes Hvcor14b And mentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed enrichment of the CBF binding site among evening-phased genes in all conditions except LDHH. The CBF family of transcription factors is strongly associated with the circadian clock, providing temperature input by directly binding the LUX promoter (Suzuki et al, 2005;Lee & Thomashow, 2012;Chow et al, 2014;Gierczik et al, 2017). Neither the G-box nor the CRT element was overrepresented under photocycles alone.…”
Section: Researchmentioning
confidence: 99%
“…Overwintering plants have high plasticity to adapt to cooling [ 2 ] at multiple points during their life cycle from seed germination to transition from vegetative to reproductive phase and flowering. The cold acclimation process is also controlled by the circadian clock, day length, and illumination depending on both light intensity and spectral composition [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%